Relative age effect in the girls` volleyball U18 world championship - Campos, F. A. D.; Pellegrinotti, I. L.; Campos, L. C. B.; Dias, T. M. R.; Gómez, M.-A. (Journal of Human Kinetics, 2020)
The relative age effect (RAE), within the sporting scope, refers to the possible advantages of participation and performance of athletes born in the first months of the year of selection in relation to others within the same age category. The aim of the present study was to investigate the RAE in girls` volleyball players participating in the U-18 World Championship, analysing the differences between the medal teams and other teams in the tournament, and considering this phenomenon in relation to the continents. Data collection was obtained from the website of the International Volleyball Federation with a sample made of 1654 youth players in the last six world championships (2007, 2009, 2011, 2013, 2015 and 2017). A greater representation of athletes born in the first months of the year of all the world championships was observed. In the comparison among the continents, it was observed that in Africa, there was a more equal distribution of quartiles compared to America, Asia and Europe. It should be noted that there was a higher percentage of medalist athletes born at the beginning of the year in comparison to the countries that placed in the last three positions of the championship. Therefore, in U-18 female volleyball, there is an advantage to have the closest birth age at the beginning of the competitive biennium.